2014
DOI: 10.1142/s2010132514500151
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of a Loudspeaker Driven 10-W Cooling Power Thermoacoustic Refrigerator

Abstract: The design and optimization procedure for a loudspeaker driven 10-W cooling power thermoacoustic refrigerator components with a temperature di®erence of 120 K has been discussed using the linear thermoacoustic theory. The resonator losses are proportional to surface area and the optimum diameter ratio of small and large resonator tubes for minimum heat loss for a quarterwavelength hemispherical ended resonator design is discussed. The hemispherical ended resonator design is further analytically optimized to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Thermo-physical properties of the refrigerator components materials (at P = 10 bar, T mg = 266 K and f = 400 Hz) chosen in the DeltaEC simulation modelling. elsewhere [19,21,22]. The variation of dynamic pressure amplitude P a , volume velocity U, acoustic power input W a and solid material temperature T s , along the length of a 50 W, k/4-TDH resonator design is shown in figure 6.…”
Section: Deltaec Modelling Results and Analysismentioning
confidence: 99%
“…Thermo-physical properties of the refrigerator components materials (at P = 10 bar, T mg = 266 K and f = 400 Hz) chosen in the DeltaEC simulation modelling. elsewhere [19,21,22]. The variation of dynamic pressure amplitude P a , volume velocity U, acoustic power input W a and solid material temperature T s , along the length of a 50 W, k/4-TDH resonator design is shown in figure 6.…”
Section: Deltaec Modelling Results and Analysismentioning
confidence: 99%
“…In the past research work, it was found that the highest stack COP and cooling power and the lowest cold heat exchanger temperature were found at the stack center position X close to the loudspeaker. 2,4,6 But it is very di±cult to fabricate small length spiral pores heat exchangers (less than 5 mm). Also, it is not practically possible to attach loudspeaker and to mount instrumentation with the smaller spacing length (less than 20 mm) available between loudspeaker and hot heat exchanger.…”
Section: Design For Manufacturementioning
confidence: 99%
“…In our past research work, design and optimization of the stack, heat exchangers, resonator and the loudspeaker using linear thermoacoustic theory have been carried out. [6][7][8] There are many types of stack, viz., spiral, circular, parallel plate, etc. In the current research work, we have chosen the spiral stack because of its simplicity in construction and because its optimized performance at 75% porosity is on par with the parallel plate one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They optimized the COP of stack and reported a value of 2.5. Prashantha et al, [15,16] designed and optimized the loud speaker driven 10W cooling power TAR for a ∆T of 120K using linear thermoacoustic theory and also explained the theoretical design procedure for optimizing the resonator. The same model is simulated by using DeltaEC which estimates -47 o C and -48 o C are the lowest temperatures for the convergent-divergent and hemispherical resonator designs respectively.…”
Section: Introductionmentioning
confidence: 99%